2019
DOI: 10.1088/1367-2630/ab2476
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical substitution on broadband dielectric response of barium-lead M-type hexaferrite

Abstract: We report on the electrodynamic properties of the single crystalline lead-substituted M-type barium hexaferrite, Ba 0.3 Pb 0.7 Fe 12 O 19 , performed in the broad frequency range including radio-frequency, terahertz and sub-terahertz bands, which are particularly important for the development of microelectronic devices. We demonstrate how changing on a molecular level the chemical characteristics (composition, intermolecular interaction, spin-orbital interaction) of lead-substituted M-type hexaferrite influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…For an extended picture of the IR phonon resonances for both compounds under study, see Supplemental Information, section SI2. The spectral response of the lattice vibrations observed in our compound is in line with the results obtained in other isostructural phases, such as the pure BaM 21 and Pb-substituted Ba 0.3 Pb 0.7 Fe 12 O 19 23 . The resonances in the spectra were modeled by Lorentzian expressions for the complex permittivity * ( )…”
Section: Broad-band Electromagnetic Spectrum Of Ba 1-x Pb X Fe 12 O 19supporting
confidence: 90%
See 2 more Smart Citations
“…For an extended picture of the IR phonon resonances for both compounds under study, see Supplemental Information, section SI2. The spectral response of the lattice vibrations observed in our compound is in line with the results obtained in other isostructural phases, such as the pure BaM 21 and Pb-substituted Ba 0.3 Pb 0.7 Fe 12 O 19 23 . The resonances in the spectra were modeled by Lorentzian expressions for the complex permittivity * ( )…”
Section: Broad-band Electromagnetic Spectrum Of Ba 1-x Pb X Fe 12 O 19supporting
confidence: 90%
“…SI5-3), we were not able to detect any sign of the domain polarity, that is most probably beyond the sensitivity of the used technique. This last suggestion is confirmed by the low values of dielectric strengths of the two relaxations, III and IV, Δε<≈10, which is by orders of magnitude less than those seen in pure BaM (Δε≈1000) 23 . We also note a considerable difference in activation energies of these relaxations, 18 meV (III) and 43 meV (IV).…”
Section: Broad-band Electromagnetic Spectrum Of Ba 1-x Pb X Fe 12 O 19mentioning
confidence: 61%
See 1 more Smart Citation
“…Magnetic oxides, containing iron ("ferrites"), crystallize in different structures. These materials are widely utilized or are promising candidates to be incorporated in various electronic devices owing to their magnetic, insulating, magnetoelectric and multiferroic properties [45][46][47][48][49][50][51] . An example of single crystal grown for our study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…x 0 62, 0 75, 1 15 (this work and 61 ). The terahertz spectra of Ti-or Pb-substituted compounds were found to be determined mainly by electronic transitions of the tetrahedrally coordinated Fe 2+ ions (for details see 51 ). According to the charge compensation mechanism, in Ti 4+ -substituted BaFe 12-x Ti x O 19 hexaferrites with < .…”
mentioning
confidence: 99%